ACCOUNTABILITY FOR THE RELATIONSHIP BETWEEN ZAKAT LITERACY, OPERATING PROFIT, AND THE INTEREST OF MSMES IN PAYING ZAKAT THROUGH ZAKAT MANAGEMENT ORGANIZATION - Dahlia Tri Anggraini; Siti Hartinah; Rindu Ferdina Lestari (Universitas Jember, 2022)
Zakat is the key to poverty alleviation efforts, tackling social problems to empowering micro-economics in addition to funds from the APBN. It is hoped that there will be a joint movement including from MSME actors. The purpose of this study was to examine and analyze the effect of accountability on the relationship between literacy, operating profit, and the interest of MSMEs in paying zakat through Zakat Management Organization (ZMO). With the stages of research; survey in the form of distributing questionnaires and interviews to the respondents (MSME entrepreneurs); processing data on the distribution of questionnaires using the SmartPLS 3 software; and data analysis. The results of this study are that zakat literacy has no significant positive effect, operating profit and accountability has a significant positive effect. This research has an implication by this research, MSME in Cipadu Market have a good zakat literacy, but they aren't familiar with ZMO. Accordingly, ZMO must be active in socializing their program to muzakki, especially MSMEs. The expectations are that MSMEs will become muzakki and will pay their zakat from their operating income through ZMO. So that it can increase the realization of zakat funds collected through ZMO in Indonesia.Keywords: Accountability, Literacy, Net Income, MSMEs, ZMO ABSTRAKZakat menjadi kunci upaya pengentasan kemiskinan, penanggulangan masalah sosial hingga pemberdayaan ekonomi mikro selain dana dari APBN. Melalui zakat, diharapkan terdapat gerakan bersama termasuk dari para pelaku UMKM. Tujuan penelitian ini adalah untuk menguji dan menganalisis pengaruh akuntabilitas terhadap hubungan literasi, laba usaha, dan minat UMKM membayar zakat melalui Zakat Management Organization (ZMO). Dengan tahapan penelitian; survei berupa penyebaran kuesioner dan wawancara kepada responden (pengusaha UMKM); pengolahan data penyebaran kuesioner menggunakan software Smart PLS 3; dan analisis data. Hasil dari penelitian ini adalah literasi zakat berpengaruh positif tidak signifikan, laba usaha dan akuntabilitas berpengaruh positif signifikan. Penelitian ini memiliki implikasi praktis bahwa meskipun UMKM di Pasar Cipadu memiliki literasi zakat yang baik, tetapi mereka tidak mengenal ZMO. Oleh karena itu, ZMO harus aktif mensosialisasikan programnya kepada para muzakki, khususnya UMKM. Harapannya, UMKM akan menjadi muzakki dan akan membayar zakat dari hasil usaha mereka melalui ZMO. Sehingga dapat meningkatkan realisasi dana zakat yang terkumpul melalui ZMO di Indonesia.Kata Kunci: Akuntabilitas, Laba Bersih, Literasi, UMKM, ZMO